External validation of the Canadian Syncope Risk Score for patients presenting with undifferentiated syncope to the emergency department. (13th October 2020) - Chan, Jason; Ballard, Emma; Brain, David; Hocking, Julia; Yan, Alan; Morel, Douglas; Hunter, Jonathan
Abstract: Objective: To validate the accuracy and safety of the Canadian Syncope Risk Score (CSRS) for patients presenting with syncope. Methods: Single centre prospective observational study in Brisbane, Australia. Adults presenting to the ED with syncope within the last 24 h were recruited after applying exclusion criteria. Study was conducted over 1 year, from March 2018 to March 2019. Thirty‐day serious adverse events (SAE) were reported based on the original derivation study and standardised outcome reporting for syncope. Individual patient CSRS was calculated and correlated with 30‐day SAE and disposition status from ED. Results: Two hundred and eighty‐three patients were recruited to the study. Average age was 55.6 years (SD 22.7 years), 37.1% being male with a 39.9% admission rate. Thirty‐day SAE occurred in seven patients (2.5%) and no recorded deaths. The CSRS performed with a sensitivity of 71.4% (95% confidence interval [CI] 30.3–94.9%), specificity 72.8% (95% CI 67.1–77.9%) for a threshold score of 1 or higher. Conclusion: Syncope patients in our study were predominantly very low to low risk (72%). The prevalence of 30‐day SAE was low, majority occurring following hospital discharge. Sensitivity estimates for CSRS was lower than the derivation study but lacked robustness with wide CIs because of a small sample size and number of events observed. However, the CSRS did not miss any clinically relevant outcomes in low risk patients making it potentially useful in aiding their disposition. Larger validation studies in Australia are encouraged to further test the diagnostic accuracy of the CSRS. Abstract : External validation of the Canadian Syncope Risk Score in Australia demonstrating a sensitivity of 71.4% (95% confidence interval [CI] 30.3–94.9) and specificity of 72.8% (95% CI 67.1–77.9) for threshold score of 1. Low 30‐day SAE (2.5%) and no deaths. Majority of patients were low risk and could potentially avoid hospitalisation safely.